Elasmobranch bycatch associated with the shrimp trawl fishery off the Pacific coast of Costa Rica, Central America - Clarke, Tayler McLellan (2015)
Demersal sharks and rays are common yet vulnerable components of the bycatch in tropical bottom-trawl fisheries. Little is known about the elasmobranch assemblages associated with most of these fisheries, particularly within the eastern tropical Pacific. This study characterized the elasmobranch assemblage associated with the shrimp trawl fishery along the Pacific coast of Costa Rica. Between August 2008 and August 2012, 346 trawl hauls were conducted at depths of 18–350 m. These hauls resulted in a sample of 4564 elasmobranchs from 25 species and 13 families. The Panamic stingray (Urotrygon aspidura), rasptail skate (Raja velezi), brown smoothhound (Mustelus henlei), and witch guitarfish (Zapteryx xyster) accounted for more than 66% of the elasmobranch abundance within the bycatch. Depth was the main factor influencing the elasmobranch assemblage; species richness was significantly higher at depths <100 m than at other depths. Two groups of elasmobranchs were identified: the first was found in shallow waters (<50 m), and the second was observed at depths of 50–350 m. Sex and size segregation patterns are also influenced by depth. Moreover, we documented the shift of the bottomtrawl fishery toward shallow-water resources—a change that could be problematic considering that elasmobranch diversity is higher in shallow waters